Peran Komunikasi Interpersonal Dalam Meningkatkan Efektivitas Rekrutmen Kandidat di PT Sunrecuit Indonesia - Ayu Setyowati; Muhammad Ichsan; Chepi Nurdiansyah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
PT Sunrecruit Indonesia is a company engaged in the recruitment service (headhunter) industry, focusing on providing qualified candidates according to clients’ needs across various industries. The recruitment process in this company not only relies on digital media sourcing but also emphasizes effective interpersonal communication between recruiters, candidates, and clients. This study aims to analyze how interpersonal communication, which consists of openness, empathy, positive attitude, equality, and support, can improve recruitment effectiveness, including time to hire, candidate quality, recruitment cost, client satisfaction, and candidate retention. The data collection methods used in this research include observation, in- depth interviews, and literature study, with a descriptive qualitative analysis method. The results show that the application of good interpersonal communication by recruiters has a positive impact on recruitment efficiency, the quality of recommended candidates, and client satisfaction and loyalty. Furthermore, effective interpersonal communication helps minimize misunderstandings and obstacles during the recruitment process, thus improving candidate retention in client companies.